In Vivo Study On Preventive Effects Of Polyalthia Longifolia Bioformulations Against Black Scurf Disease Of Potato (SAARC Journal of Agriculture, 2024)
Bioformulation prepared by combining Polyalthia longifolia leaf extract with elicitors (neem oil cake) and binders (cow dung) were tested for management of black scurf disease of potato caused by Rhizoctonia solani. Two different application methods- seed dipping and soil amendment were used for in vivo study. The preventive action was studied as a function of decrease in disease severity by PDI (Percent Disease Index) and PEDC (Percent Efficiency of Disease Control) methods. Change in growth characteristics of host plant such as number of leaves/plant, plant height, number of branches/plant, number of flower/plant, number of fruit/plant and weight of fruits were recorded in control and treated plants. Six treatments T1 (formulation no.12 ), T2 (formulation no.7 ), T3 (formulation no.26 ), T4 (formulation no.17) were applied in different combinations and four different control were also maintained. Potato plants were examined for symptoms infected tuber (sclerotia) were quantitatively assessed after 90 DAS (days after sowing). Results of present study indicates that treatment with bioformulation especially T4 treatment not only reduces the infection but also leads to increased growth, health and vigour of the host plant as compared to untreated and synthetic fungicide control. Results were subjected to statistical analysis of student t test, one way ANOVA and post-Hoc comparisons analysis. Significance was measured at p